Entrustable professional activities: A useful concept for neurology education. (13th February 2018) - Horak, Holli; Englander, Robert; Barratt, Diana; Kraakevik, Jeff; Soni, Madhu; Tiryaki, Ezgi
Abstract : Medical education is currently undergoing a paradigm shift from process-based to competency-based education, focused on measuring the desired competence of a physician. In an attempt to improve the assessment framework used for medical education, the concept of entrustable professional activities (EPAs) has gained traction. EPAs are defined as professional activities that can be entrusted to an individual in a clinical context. The Association of American Medical Colleges (AAMC) defined a set of 13 such EPAs to define the core of what all students should be able to do on day 1 of residency, regardless of specialty choice. The AAMC is currently piloting these EPAs with 10 medical schools to determine if EPAs can be used as a way to observe, measure, and entrust medical students with core clinical activities by the end of the clinical immersion experiences of the third year. The specialty of pediatrics is piloting the use of specialty-specific EPAs at 5 medical schools to assess readiness for transitions from medical school into pediatric residency training and practice. To date, no neurology-specific EPAs have been published for use in neurology clerkships or neurology residencies. This article introduces the concept of EPAs in the context of competency-based medical education and describes how EPAs might be relevant and applicable in neurologic education across the continuum. The Undergraduate Education Subcommittee of the American Academy of Neurology advocates for a proactive approach to incorporating core EPAs in undergraduate medical education and to considering an EPA-based specialty-specific assessment framework for neurology.